A sense of belonging helps! The alleviating effect of national identification on burnout among diplomats. Issue 1 (10th December 2021) - Zhang, Ling Eleanor; Lauring, Jakob; Liu, Ting
Abstract : Purpose: This paper aims to explore the interplay between burnout, national identity and career satisfaction among diplomats. In particular, the authors focus on the roles of home and host country identification as an emotional resource for overcoming the negative effects of job-related burnout. Design/methodology/approach: Survey responses from 123 diplomats were used to assess the moderating role of home and host country identification on the relationship between burnout and career satisfaction. Findings: Various combinations of high or low home or host country identification were tested, and the findings suggest that the negative effect of burnout on career satisfaction is reduced for those individuals that have high identification with both the home and the host country, while this is not the case for other combinations. This points to the beneficial effects of dual national identifications even for diplomats – a group that would normally be expected to identify strongly with the home country alone. Originality/value: No existing study that the authors know of has explored the relationship between burnout, national identity and career satisfaction among diplomats or other types of expatriates. This is unfortunate because a better understanding of national identity could guide practitioners in finding ways to reduce the negative consequences of burnout in international organizations.